2018
DOI: 10.23880/jidtm-16000118
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A Virus Infection Alters Gut Microbiota Composition in Juvenile Mice

Abstract: The gut microbiota (GM) stimulates the immune system to facilitate appropriate immune responses at local and distal sites of virus infection. However, the impact of distal virus infections in modulating the composition of GM is less clear.Here, a mouse model was used to examine the effect of influenza a virus (IAV) infection on the composition of GM in mice that did or did not receive oral treatment with broad spectrum antibiotics (ABX). We focused on ABX treatment of 3 weeks old juvenile mice, as this represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(64 reference statements)
1
0
0
Order By: Relevance
“…In addition, interferon production in the lungs have also been reported to alter the composition of intestinal microbes (Wang et al, 2014 ; Deriu et al, 2016 ). Similar to previous studies (Fuglsang et al, 2018a , b ), we found that the abundance of A. muciniphila significantly increased after influenza infection. A recent literature has shown that influenza infection enhanced intestinal Muc2 levels (Deriu et al, 2016 ), which may be related to the upregulation of A. muciniphila , due to muc2 is an essential ingredient to maintain the growth of A. muciniphila .…”
Section: Discussionsupporting
confidence: 92%
“…In addition, interferon production in the lungs have also been reported to alter the composition of intestinal microbes (Wang et al, 2014 ; Deriu et al, 2016 ). Similar to previous studies (Fuglsang et al, 2018a , b ), we found that the abundance of A. muciniphila significantly increased after influenza infection. A recent literature has shown that influenza infection enhanced intestinal Muc2 levels (Deriu et al, 2016 ), which may be related to the upregulation of A. muciniphila , due to muc2 is an essential ingredient to maintain the growth of A. muciniphila .…”
Section: Discussionsupporting
confidence: 92%